2015
DOI: 10.1371/journal.pone.0137914
|View full text |Cite
|
Sign up to set email alerts
|

Statins Reduces the Risk of Dementia in Patients with Late-Onset Depression: A Retrospective Cohort Study

Abstract: ObjectivePatients with late-onset depression (LOD) have been reported to run a higher risk of subsequent dementia. The present study was conducted to assess whether statins can reduce the risk of dementia in these patients.MethodsWe used the data from National Health Insurance of Taiwan during 1996–2009. Standardized Incidence Ratios (SIRs) were calculated for LOD and subsequent dementia. The criteria for LOD diagnoses included age ≥65 years, diagnosis of depression after 65 years of age, at least three servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…Previously, we have used the NHIRD database to study the association of statin with risk of dementia [15]. We found that statins may reduce the risk of subsequent dementia in patients with LOD [15]. Similarly, Wu et al have also reported the association of statins with reduced risk of dementia in elderly patients [16].…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Previously, we have used the NHIRD database to study the association of statin with risk of dementia [15]. We found that statins may reduce the risk of subsequent dementia in patients with LOD [15]. Similarly, Wu et al have also reported the association of statins with reduced risk of dementia in elderly patients [16].…”
Section: Introductionmentioning
confidence: 66%
“…Interestingly, LOD frequently arises in the context of vascular disorders [10][11][12], and it has been proposed complex vulnerability models involving endothelial dysfunction interacting with other complex multidirectional ways to mediate depression [13,14]. Previously, we have used the NHIRD database to study the association of statin with risk of dementia [15]. We found that statins may reduce the risk of subsequent dementia in patients with LOD [15].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although studies have shown that statins can reduce the severity of inflammation and improve patient response to ESA, we previously found that response to CERA was not dependent on treatment (such as statin or iron supplement therapy) but on parameters of the clinical response (such as cholesterol and ferritin) to treatment that influenced the erythropoiesis . For this reason, usage of statins or iron supplements was not recorded in this study.…”
Section: Introductionmentioning
confidence: 78%
“…Seven cohort studies (Chen et al, ; Chuang, Lin, Lin, Sung, & Kao, ; Hendrie et al, ; Hippisley‐Cox & Coupland, ; Li et al, ; C.‐K. Wu et al, ; Yang et al, ) and five case control studies (Booker et al, ; Chen, Liu, Chen, & Wu, ; Corrao et al, ; Horsdal et al, ; Lin et al, ) found that statin use was associated with a reduced risk of dementia. According to these studies, beginning treatment with high doses of lipophilic statins before an early old age (<80 years old) and taking these statins for a long time might reduce the risk of dementia.…”
Section: Resultsmentioning
confidence: 99%